The application of exosomes in the treatment of triple-negative breast cancer - Weaver, John W.; Zhang, Jinyu; Rojas, Juan; Musich, Phillip R.; Yao, Zhiqiang; Jiang, Yong (Frontiers in Molecular Biosciences, 2022)
Triple-negative breast cancer (TNBC) is a heterogeneous and invasive breast cancer (BC) subtype that is estrogen receptor-negative, progesterone receptor-negative, and human epidermal growth factor receptor 2 (Her2)-negative. So far, the treatment of TNBC is still ineffective due to the lack of well-defined molecular targets. Exosomes are nanosized extracellular vesicles composed of lipid bilayers. They originate from various types of donor cells and release a complex mixture of contents including diverse nucleic acid types (miRNA, LnRNA, siRNA, and DNA) and proteins; after binding to recipient cells the exosomes release their contents that execute their biological functions. Exosomes have been reported to play an important role in the tumorigenesis of TNBC, including tumor initiation, metastasis, angiogenesis, cell proliferation, immune escape, and drug resistance. On the other hand, exosomes can be valuable biomarkers for diagnosis, monitoring, and treatment of TNBC. More interestingly, exosomes can be harnessed as a nanosized drug-delivery system specifically targeting TNBC. In this review, we present the most recent mechanistic findings and clinical applications of exosomes in TNBC therapy, focusing on their use as diagnostic and prognostic biomarkers, nanoscale drug delivery platforms, and immunotherapeutic agents. In addition, the associated challenges and future directions of using exosomes for TNBC treatment will be discussed.